Acessibilidade e calçadas à luz do direito à cidade: uma avaliação das políticas urbanas em Fortaleza (2013-2020) - Diogo, Tatiana Barroso Camelo (2021)
The democratization of urban spaces, and the microaccessibility, ensures people with disabilities or reduced mobility basic rights that permeate the dignity of the human person. Many countries, following international conventions on people with disabilities, have sought adaptations that would make urban spaces more inclusive, in Brazil, it was no different, however, despite the legislative advancements, there are few truly accessible spaces. Given the importance of the topic, this research proposed to evaluate, considering the constitutional guarantees and the right to the city, urban policies implemented in the city of Fortaleza, during the 2013-2020 period, regarding the accessibility of sidewalks. The methodology design of this investigation relied on the use of reflective and experiential assessment, in articulation with case study assessment. The research focuses on the analysis of urban sectorial policies that have repercussions in the micro-accessibility. The methodology adopted made use of a qualitative assessment, through bibliographic and documental research, considering national and local legislation and the case study of the 'Plano de Ação Novo Centro', an intervention for downtown Fortaleza. It was found that the legislation currently in effect provides the public manager with greater legal security for the actions necessary to make the city more inclusive. It was also observed a change in attitude of the public management and part of the population regarding their responsibilities in achieving this right. However, many aspects of social complexity and of technical and legal norms, essential to achieve universal accessibility, are still neglected in the planning and implementation of urban policies. Such non-observance makes the materialization of advances insufficient to meet the real needs of people with disabilities.